Odpowiedzi

Najlepsza Odpowiedź!
2010-02-08T16:14:33+01:00
A)
0,1 x + 0,2 = - 0,3
0,1x=-0,3-0,2
0,1x=-0,5
x=-5

b)
0,25 x + 0,4 = 0,35
0,25x=0,35-0,4
0,25x=-0,05
x=-0,2

c)
1 - 0,2 x = - 0,3
-0,2x=-0,3-1
-0,2x=-1,3
x=6,5

d)
0,01 x - 1 = 0,1 x - 0,1
0,01x-0,1x=-0,1+1
-0,09x=0,9
x=-10
2010-02-08T16:17:15+01:00
A) 0,1 x + 0,2 = - 0,3
0,1 x = - 0,3 - 0,2
0,1x = -0,5 / : 0,1
x = - 1/2 : 1/10 = - 1/2 * 10 /1 = - 5
b) 0,25 x + 0,4 = 0,35
0,25 x = 0,35 - 0,4
0,25x = - 0,05 / 0,25
x= -5/100 : 25/100 = -1/20 * 4 /1 = -1/5
c) 1 - 0,2 x = - 0,3
- 0,2 x = - 0,3 - 1
-0,2x= -1,3 / -0,2
x= 13/10 : 2/10= 13/10 * 10/2 = 13/2 = 6 1/2

d) 0,01 x - 1 = 0,1 x - 0,1
0,01 x - 0,1 x = 1 - 0,1
-0,09x = 0,9 / : (-0,09)
x = 9/10 : (- 9/100)= - 9/10 * 100/9 = -10
1 5 1